Effectiveness and mechanisms of lymphocytes at different time points in predicting consolidation immunotherapy following adaptive chemoradiotherapy in locally advanced non-small cell lung cancer - Sun, Zhen wei; Duan, Jiayi; Zhang, Zhaohao; Chen, Meng; Zhou, Dandan; Hou, Liqiao; Gu, Pingjun; Zhu, Jian; Yang, Haihua; Zhou, Suna (Frontiers in Oncology, 2026)
ObjectiveTo investigate the prognostic value of lymphocytes and their subsets at different stages of chemoradiotherapy and consolidation immunotherapy in patients with locally advanced non-small cell lung cancer (NSCLC).MethodsThis retrospective analysis enrolled 139 patients with stage III NSCLC (median age 69 years; 95% male; 84.17% squamous cell carcinoma) who received adaptive chemoradiotherapy (CRT) and consolidation anti-PD-1 therapy (sintilimab). Paired samples t-tests were performed to evaluate differences in absolute lymphocyte counts (ALCs) at three time points: before radiotherapy, at the 20th fraction of radiotherapy, and 1 month after radiotherapy. Additionally, paired t-tests were used to compare lymphocyte subsets between the pre-radiotherapy period and 1 month post-radiotherapy. Univariate and multivariate Cox proportional hazards regression analyses were conducted to identify factors influencing progression-free survival (PFS) and overall survival (OS). The Kaplan–Meier analysis was employed to assess PFS and OS in patients stratified according to independent predictive factors associated with OS.ResultsStatistically significant differences were observed in ALCs among the three time points before radiotherapy, at the 20th fraction of radiotherapy, and 1 month after radiotherapy (p < 0.05). Univariate and multivariate analyses identified ALCs at 1 month post-radiotherapy, ALC decrease (defined as the difference between pre-radiotherapy and the 20th fraction of adaptive radiotherapy), and ALC increase (defined as the difference between the 20th fraction and pre-radiotherapy) as independent predictors of OS (p < 0.05). The Kaplan–Meier curves demonstrated that patients with ALCs > 1.015 × 109/L at 1 month after radiotherapy, an ALC decrease > 0.71 × 109/L, or an ALC increase > 0.305 × 109/L had significantly longer OS. Significant differences were also observed in CD4+ and CD8+ counts, as well as the CD8/CD4 ratio, between pre-radiotherapy and 1 month post-radiotherapy (p < 0.05). The Kaplan–Meier analysis further showed that patients with higher CD8+ T-cell counts at 1 month post-radiotherapy had significantly longer OS (p < 0.05).ConclusionIn patients with locally advanced NSCLC receiving chemoradiotherapy followed by consolidation immunotherapy, higher ALCs and elevated CD8+ T-cell counts at 1 month post-chemoradiotherapy are associated with improved overall survival.